Testing and calibration of commercial wattmeters - Kirby, A. W.; Marshall, P. E. (My University, 1908)
Introduction: The importance of reliable measurement of electrical power is at once evident. The increasing demand for electrical power has made it necessary that a unit of power be established, and that instruments be made that will accurately measure this power. It was because of this demand that the integrating wattmeter was invented.
Citation: Kirby, A. W. and Marshall, P. E. Testing and calibration of commercial wattmeters. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Electricity; Engineering; Power; Graduating theses; Senior theses; Theses